1997
DOI: 10.1007/bf01273322
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic distribution of brainstem substance P binding sites in humans: Ontogenic study and relation to Sudden Infant Death Syndrome (SIDS)

Abstract: The precise distribution of substance P (SP) binding sites in the human brainstem was investigated in normal cases (3 fetuses and 24 new-borns) and in 9 cases of Sudden Infant Death Syndrome (SIDS) by in vitro quantitative autoradiography. We discussed the widely but uneven distribution of SP binding sites as regards to the role of SP in brainstem cardio-respiratory ontogenic control and its possible involvement in SIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…In keeping with initial reports, Bergstrom et al [136] found no difference in Met-enkephalin concentration between SIDS and controls in medulla, pons, hypothalamus or cortex, but disclosed for the first time a significant increase in the concentrations of substance P in the medulla of SIDS infants [136]. In contrast, a more recent study on substance P in the brain stem of SIDS infants [138] indicated that there were no significant differences between SIDS and developmentally normal infants. In contrast, a more recent study on substance P in the brain stem of SIDS infants [138] indicated that there were no significant differences between SIDS and developmentally normal infants.…”
Section: Brain Stemsupporting
confidence: 58%
“…In keeping with initial reports, Bergstrom et al [136] found no difference in Met-enkephalin concentration between SIDS and controls in medulla, pons, hypothalamus or cortex, but disclosed for the first time a significant increase in the concentrations of substance P in the medulla of SIDS infants [136]. In contrast, a more recent study on substance P in the brain stem of SIDS infants [138] indicated that there were no significant differences between SIDS and developmentally normal infants. In contrast, a more recent study on substance P in the brain stem of SIDS infants [138] indicated that there were no significant differences between SIDS and developmentally normal infants.…”
Section: Brain Stemsupporting
confidence: 58%
“…, ; Prandota ; Vege and Ole Rognum ; Kinney and Thach ) and upregulation of inflammatory mediators, such as IL‐1 β and substance P, is assumed to be responsible for SIDS (Jordan et al. ; Froen et al. ; Balan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous physiological studies on SP‐mediated or ENK‐mediated respiratory activity, the present study, using morphological approaches to identify SP or ENK immunoreactivity and their relationship with neurotransmitters, as well as with NK1R‐ir neurons in the pre‐BötC, provides a foundation for understanding synaptic interaction underlying respiratory rhythmogenesis and modulation in the pre‐BötC network. Alteration of SP‐mediated or ENK‐mediated synaptic transmission may implicate respiratory disorders such as sudden infant death syndrome (Morin‐Surun et al ., 1992; Jordan et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%